The relationship between housing subsidies and supportive housing on neighborhood distress and housing satisfaction: does drug use make a difference?. Issue 1 (December 2016) - Dickson-Gomez, Julia; McAuliffe, Timothy; Obidoa, Chinekwu; Quinn, Katherine; Weeks, Margaret
Abstract Background Since the 1970s, the dominant model for U.S. federal housing policy has shifted from unit-based programs to tenant-based vouchers and certificates. Because housing vouchers allow recipients to move to apartments and neighborhoods of their choice, such programs were designed to improve the ability of poor families to move into neighborhoods with less concentrated poverty. However, little research has examined whether housing voucher recipients live in less distressed neighborhoods than those without housing vouchers. There is much reason to believe that drug users may not be able to access or keep federal housing subsidies due to difficulties drug users, many of whom may have criminal histories and poor credit records, may have in obtaining free market rental housing. In response to these difficulties, permanent supportive housing was designed for those who are chronically homeless with one or more disabling condition, including substance use disorders. Little research has examined whether residents of permanent supportive housing units live in more or less economically distressed neighborhoods compared to low-income renters. Methods This paper uses survey data from 337 low-income residents of Hartford, CT and geospatial analysis to determine whether low-income residents who receive housing subsidies and supportive housing live in neighborhoods with less concentrated poverty than those who do not. We also examine the relationships between receiving housing subsidies or supportive housing and housing satisfaction. Finally, we look at the moderating effects of drug use and race on level of neighborhood distress and housing satisfaction. Results Results show that low-income residents who receive housing subsidies or supportive housing were not more or less likely to live in neighborhoods with high levels of distress, although Black residents with housing subsidies lived in more distressed neighborhoods. Regarding housing satisfaction, those with housing subsidies perceived significantly more choice in where they were living while those in supportive housing perceivedless choice. In addition, those with rental subsidies or supportive housing reported living closer to needed services, unless they also reported heavy drug use. Conclusions Housing subsidies and supportive housing have little impact on the level of neighborhood distress in which recipients live, but some effects on housing satisfaction.